The Impact of Initial Misdiagnosis of Ruptured Abdominal Aortic Aneurysms on Lead Times, Complication Rate, and Survival. (July 2017) - Smidfelt, K.; Drott, C.; Törngren, K.; Nordanstig, J.; Herlitz, J.; Langenskiöld, M.
Abstract : Objective/Background: To investigate the frequency of initial misdiagnosis and the clinical consequences of an initial misdiagnosis of ruptured abdominal aortic aneurysms (rAAA). Methods: This was a retrospective cohort study. Data from the Swedish National Registry for Vascular Surgery (Swedvasc) and medical charts were extracted for patients treated for rAAA in the West of Sweden in the period 2008–14. Initially misdiagnosed patients were compared with correctly diagnosed patients. Results: In all, 261 patients were included in the study. Patients with rAAA were initially misdiagnosed in 33% ( n  = 86) of the cases and this caused a 4.8 hour (median time) additional delay to surgical intervention. There were no differences in 30 day mortality between initially misdiagnosed patients and correctly diagnosed patients (27.9% vs. 28.0%; p  = 1.00). The adjusted odds ratio for mortality in initially misdiagnosed patients compared with correctly diagnosed patients was 0.78 (95% confidence interval 0.38–1.60). No difference was observed between the groups regarding 90 day mortality, length of intensive care, need for post-operative ventilator support, need of haemodialysis support, and length of hospital stay. Conclusion: Misdiagnosis is common in patients with rAAA, and treatment is significantly delayed in misdiagnosed patients. The study did not show any survival disadvantage or increased frequency of post-operative complications in misdiagnosed patients despite the delayed treatment. However, only patients who reached surgical intervention were included in the analysis.